Upaya Meningkatkan Kemampuan Melakukan Kontak Mata Melalui Metode ABA (Applied Behavior Analysis) pada Siswa Autis Ringan Kelas III di SLB Bhakti Luhur Atambua - Tobing, Johana Feriana; Selan, Ot Bil Wilson; Wangge, Vinsensius (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The ability to make eye contact is a fundamental component of social communication that is often impaired in children with mild autism. This study aimed to describe changes in eye contact ability following the implementation of the Applied Behavior Analysis (ABA) method with a third-grade student with mild autism at SLB Bhakti Luhur Atambua. The study employed a Single-Subject Research approach, utilizing repeated measurements across baseline and intervention phases. The subject was a 10-year-old student identified by the initials OD. Data were collected through observation, tests, interviews, and documentation, and subsequently analyzed descriptively using visual analysis. The results indicated a positive change in eye contact ability during the intervention phase. During the baseline phase, the subject's scores were 45, 50, and 57, respectively, whereas during the intervention phase, the scores increased to 65, 70, and 76. These score changes demonstrate an improvement in the subject's eye contact ability following the ABA intervention, which incorporated structured instruction, prompting, fading, repetition, and positive reinforcement. These findings suggest that the implementation of ABA procedures in this study is associated with positive changes in the subject's eye contact ability.